The quality of democracy revisited: exploring the effects of government alternation and presidential power in Latin America - Hernandez Gonzalez, Manuel (2024)
This dissertation explores two possible causes of the quality of democracy in Latin America: government alternation and presidential power. For that purpose, this work selects 12 of the presidential systems of the Latin American region that will be the focus of the study: Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, Mexico, Paraguay, Peru, Uruguay and Venezuela. The period to be covered is set between 1974 and 2019, using the beginning of the “third wave of democratisation” as the starting point. The unit of analysis that I will observe is the democratic years within the selected period. These years are determined using the criteria of the Varieties of Democracy, Polity IV and Freedom House indexes. This dissertation opens with Chapter 1 as an introduction, in which I formulate the following research question: what are the effects of government alternation and presidential power on the dimensions of the quality of democracy? Then, I develop a literature review that explores the concepts of the quality of democracy, government alternation and presidential power. In turn, this helps me to set my theoretical foundations and is an attempt to identify gaps in the literature.